I don't feel ya: How narcissism shapes empathy. Issue 2 (17th February 2021) - Burgmer, Pascal; Weiss, Alexa; Ohmann, Katharina
ABSTRACT: Those who tend towards a self-absorbed personality are less likely to "feel others." Indeed, subclinical narcissism has been linked to decreased empathy: Individuals high in narcissism seem to neglect what other people are thinking and feeling and are less likely to emotionally share others' mental states. Three studies ( N = 1, 008) extend the literature on narcissism and empathy in some important ways. We suggest that the empathy deficit among narcissists does not make an exception for close friends, that it manifests not only in less, but also in discordant affect, and that it is mainly driven by the antagonistic dimension of narcissism (Studies 1 and 2). Moreover, employing an experimental manipulation, the present findings offer a novel way of attenuating this empathy deficit among narcissists: the experience of trust (Study 2). Finally, a pre-registered laboratory study documents a "bright" consequence of narcissists' empathy deficit with respect to parochial altruism (Study 3). Hence, as unfortunate as narcissists' empathy deficit might be, it is not set in stone. Additionally, a narcissistic spotlight that shines exclusively on the self can reduce some of the parochialism that empathy for specific, often close others entails.